A Method for Deconvoluting and Quantifying the Real‐Time Species Fluxes and Ionic Currents Using In Situ Electrochemical Quartz Crystal Microbalance. Issue 16 (3rd March 2022) - Zheng, Kai; Xian, Yongqiu; Lin, Zifeng
Abstract: Electrochemical quartz crystal microbalance (EQCM) is a powerful tool to screen the gravimetric response of electrochemically active electrodes. In this study, a method is proposed to deconvolute and quantify the real‐time fluxes and ionic currents of different species based on the EQCM measurement results. This work creatively conceptualizes the flux cyclic voltammograms (CVs) and ionic current CVs, and applys them to analyze the real‐time molecules and ion evolution. As a proof of concept, Ti3 C2 T x MXene, the most studied 2D metal carbide, is investigated as a supercapacitor electrode in 1 m H2 SO4 electrolyte. The real‐time H2 O and H + fluxes are obtained using the proposed approach and corresponding flux CVs are constructed. The potential‐dependent evolution of H2 O and H + fluxes suggest that the insertion of hydrated H + contributes significantly to the double‐layer capacitance. The H + CV calculated from the H + flux overlaps with the experimental measured CV, confirming that H + is the only interactive charge carrier for screening the Ti3 C2 T x electrode charge. Abstract : This study provides a method for deconvoluting and quantifying the real‐time species population, fluxes, and corresponding ionic currents from conventional in situ electrochemical quartz crystal microbalance measurement results. Flux cyclic voltammograms (CV) and ionic current CV are proposed for better interpreting the potential‐dependent specie flux and ionic current evolution. As a proof of concept, Ti3 C2 T x MXene capacitive electrode in 1 m H2 SO4 electrolyte is investigated.